STUDI KASUS WANITA KARIR SETELAH MENIKAH: Peran Wanita Karier dalam Menjalankan Fungsi Keluarga - Tabina Naura Zayyani Tampubolon; Eno Amanda Maulani; Halsa Tirani (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
This study has several pedagogical implications. For instance, when seeking a solution or treatment of career women after marriage can be more empathy and discussion in the form of a cultural approach if there are autobiographies that narrate matters experienced during romantic relationships outside Western culture. This study has implications for the ways marriage and family education can be implemented in daily life using what is already known. At its core, this study shows that professional women are more likely to be the party who files for divorce than their non-professional counterparts. It says a lot if the career woman is going to work much harder at not getting pregnant than she would have just sat out on all the sex, which must mean her reasons for doing it are stronger than yours. Another thing is responsible conditions from the husband and external factors including a third party. The result of this study suggests the importance and impact of family and society in shaping each marriage process. This proposal shows that the marriage.